2021
DOI: 10.1556/2060.2021.00185
|View full text |Cite
|
Sign up to set email alerts
|

The use of near-infrared spectroscopy for the evaluation of a 4-week rehabilitation program in patients with COPD

Abstract: Background Near-infrared spectroscopy (NIRS) technology can evaluate muscle metabolism and oxygenation. NIRS-based oximeters can measure skeletal muscle oxygen delivery and utilization during static and dynamic work non-invasively. Our goal was to assess the value and usability of NIRS technology in chronic obstructive pulmonary disease (COPD) rehabilitation program. Methods Forty patients with COPD participated in a 4-week inpatient rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This is an important clue that the peripheral muscles of patients in the early stages of COPD are able to balance the oxygen supply and demand status using oxygen more efficiently and effectively during exercise, which is how Szucs et al explained the improvement in muscle oxygenation after pulmonary rehabilitation in patients with COPD. 30 These results obtained in muscle oxygen saturation are explained by the physical fitness status of healthy individuals, which varies according to whether they are sedentary or active, and by the fact that energy production-consumption systems have the potential to perform more work at the same oxygen levels. 31 In our study, although muscle oxygen saturation during exercise was higher in COPD patients with increasing disease severity, they performed functionally the same task as the group with less disease severity, which may be explained by the fact that energy metabolism and endurance status were affected due to decreased oxygen level and oxygen utilization capacity of the muscle with increasing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important clue that the peripheral muscles of patients in the early stages of COPD are able to balance the oxygen supply and demand status using oxygen more efficiently and effectively during exercise, which is how Szucs et al explained the improvement in muscle oxygenation after pulmonary rehabilitation in patients with COPD. 30 These results obtained in muscle oxygen saturation are explained by the physical fitness status of healthy individuals, which varies according to whether they are sedentary or active, and by the fact that energy production-consumption systems have the potential to perform more work at the same oxygen levels. 31 In our study, although muscle oxygen saturation during exercise was higher in COPD patients with increasing disease severity, they performed functionally the same task as the group with less disease severity, which may be explained by the fact that energy metabolism and endurance status were affected due to decreased oxygen level and oxygen utilization capacity of the muscle with increasing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Most biological tissues, as skin and bone, have relatively low light absorption property in this range, depending on water and lipids contess [2]. The NIRS method cannot differentiate between HbO 2 and O 2 Mb or HHb and HMb, which means that NIRS signals are the result of the weighted average of oxygen saturations of the heme group of hemoglobin (Hb) in the vascular bed (small arteries, arterioles, capillaries, venules and small veins) and the heme group of myoglobin (Mb) in the muscle fibers [3]. Differences in the oxygen-dependent absorption spectra of iron and/or copper centers in these molecules enable measurement of relative changes in the amounts of oxidized copper and oxidized forms of heme present in muscles [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that during work the degree of deoxidation of skeletal muscles varies depending on the type of muscle, type of exercise and blood flow specific to a given area and health status [27,28]. Only a few authors refer to the use of NIRS in physiotherapy as a method for assessing the impact of physical or kinesiotherapy treatment or entire rehabilitation programs in therapeutic rehabilitation [3,29,30].…”
Section: Introductionmentioning
confidence: 99%